General Legal Description and Calculation of Procedural Time Limits in Civil Proceedings - Yesayan, V. (Bulletin of Yerevan University C: Jurisprudence, 2020)
General description, concept, types and calculation of procedural time limits are discussed within the framework of the presented article. The time limits for the execution of specific legal actions, during which a judicial action can be performed, are indicated. Both the national legislative norms and a number of precedential decisions on the topic of interest have been analyzed and presented in the article.
Keywords: court, time limit, probation period, reasonable time, European court, trial, calculation of the trial time limits